A prestação de serviços ecossistêmicos e a dinâmica de estoque de dióxido de carbono no sistema de espaços livres de Belo Horizonte: estudo de caso na Regional Centro Sul - Rubens do Amaral (2015)
This dissertation seeks to study the performance of urban forests in the provision of urban ecosystem services, through the analysis of carbon sequestration, in certain areas along the Belo Horizonte's landscape. Objective so to compare the environmental effectiveness of the analyzed sections, by the production of forest biomass and carbon and nutrient sequestration in the soil. Search up with that, offers quality indicators of environmental services and support the proposal for landscape guidelines aimed at its implementation or improvement. Therefore, based on exploratory research related to landscape studies, urban morphology and restoration ecology is possible the combination of geomorphological aspects of the site, the former vegetation layer and the implementation of the anthropic system over the city. The analysis resulted in the choice of the Centro-Sul Regional Administration of Belo Horizonte for case study, as well as the urban forest sections related to Municipal Park of Mangabeiras, Raul Soares Square and Parque Municipal Americo Renne Giannetti. In these areas, were performed biomass estimation and soil samples, which were sent for laboratory testing of soil fertility, concentration of humic substances and analysis of stable isotopes. The results were analyzed critically in relation to morphological processes and the design and landscaping treatment of each area, in order to provide perception about the attributes related to the environmental performances that were found. Based on that, landscaping guidelines were established oriented for the introduction and improvement of the provision of urban ecosystem services in different parts of urban forest. The study aims thus highlighting the role of vegetation in the city, especially the arboreal, as a strategic resource. According with the management adopted in urban forest stretches, can be improved the environmental quality in the cities, mitigating the impacts resulted from the urbanization process and contributing for the proposition of an urban form aligned with the paradigm of sustainability.